SELFLESS PEOPLE CAN UNITE THE WORLD AND CHANGE IT FOR THE BETTER, THEIR MISSION IS TO ADVANCE RESEARCH TO PREPARE CHILDREN FOR THE FUTURE, PHILOSOPHY OF THE MODERN SCHOOL - Toshniyozova, Rano; Toshpulatova, Shakhruza (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY RESEARCH AND INNOVATIVE TECHNOLOGIES, 2021)
The article examines the importance of a modern approach to teaching, in particular, the theoretical and practical aspects of the implementation of educational STEAM technologies. The article briefly describes the important aspects of the innovative approach in the work of teachers.